THE RELATIONSHIP BETWEEN TELEVISION SHOWS AND IMITATION BEHAVIOR OF CHILDREN AGED 4-5 YEARS - Apriana Nur Hanifah; Siti Istiyati; Nurul Kusuma Dewi (Universitas Sebelas Maret, 2020)
The purpose of this study was to determine whether there was a relationship between the television shows that children saw on imitation behavior of children aged 4-5 years in Pojok, Mojogedang, Karanganyar. The approach in this study uses a quantitative approach with a type of correlation. This research was conducted in December 2018 by using a sample of 77 children and parents in Pojok, Mojogedang, Karanganyar. Retrieval of data from this study using questionnaires distributed to parents. The results of the hypothesis test of the Spearman Rho correlation show that the significance value is 0,000 <0.05 which means the hypothesis is accepted, namely the relationship of television shows to the imitation behavior of children aged 4-5 years in Pojok, Mojogedang, Karanganyar. The results of the Spearman Rho Hypothesis Test also show a correlation coefficient of 0.657 which means television shows had a strong influence on the imitation behavior of children. The result of the data show that the higher the television show that the children sees, the higher the imitation behavior that is raised, the lower the television show that the children sees, the lower the imitation behavior that is raised. The conclusion of this study is that television shows become models for children’s imitation behavior